2017
DOI: 10.1073/pnas.1701101114
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis JASMONATE-INDUCED OXYGENASES down-regulate plant immunity by hydroxylation and inactivation of the hormone jasmonic acid

Abstract: The phytohormone jasmonic acid (JA) is vital in plant defense and development. Although biosynthesis of JA and activation of JAresponsive gene expression by the bioactive form JA-isoleucine have been well-studied, knowledge on JA metabolism is incomplete. In particular, the enzyme that hydroxylates JA to 12-OH-JA, an inactive form of JA that accumulates after wounding and pathogen attack, is unknown. Here, we report the identification of four paralogous 2-oxoglutarate/Fe(II)-dependent oxygenases in Arabidopsis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 42 publications
6
100
0
Order By: Relevance
“…Coregulation analysis with confirmed JA pathway components identified three 2OGDs genes out of four in the DOXC46 subclade (Kawai et al, 2014) as prime candidates to perform such a reaction. In the course of this work, Caarls et al (2017) reported the partial characterization of these enzymes, named JASMONATE-INDUCED OXYGENASES 1 to 4 (JOX). Here, we performed extensive functional analysis of the three most expressed genes, encoding JAO/JOX2, -3, and -4 enzymes, focusing on leaf wounding and necrotrophic fungal challenges, and two stimuli triggering strong JA metabolism and signaling.…”
Section: Discussion Ja Oxidation By Jao Enzymes Identifies a Missing mentioning
confidence: 99%
“…Coregulation analysis with confirmed JA pathway components identified three 2OGDs genes out of four in the DOXC46 subclade (Kawai et al, 2014) as prime candidates to perform such a reaction. In the course of this work, Caarls et al (2017) reported the partial characterization of these enzymes, named JASMONATE-INDUCED OXYGENASES 1 to 4 (JOX). Here, we performed extensive functional analysis of the three most expressed genes, encoding JAO/JOX2, -3, and -4 enzymes, focusing on leaf wounding and necrotrophic fungal challenges, and two stimuli triggering strong JA metabolism and signaling.…”
Section: Discussion Ja Oxidation By Jao Enzymes Identifies a Missing mentioning
confidence: 99%
“…OPC‐8:0 undergoes three rounds of β‐oxidation to form (+)‐7‐ iso ‐JA, which itself is biologically inactive (Staswick and Tiryaki, ). Once synthesized, JA may be converted into a variety of derivatives, including methyl jasmonate (MeJA) and the main biologically active conjugate (+)‐7‐ iso ‐JA‐Ile (JA‐Ile) (Vick and Zimmerman, ; Staswick and Tiryaki, ; Fonseca et al , ; Yan et al , ; Caarls et al , ; Wasternack and Strnad, ). JA signalling regulates many diverse physiological processes and is a key regulator of the defence response to wounding, herbivory, and pathogen infection via induction of defensive metabolites and proteolytic enzymes (Farmer and Ryan, ; Rodriguez‐Saona et al , ; Howe and Jander, ) or emission of volatile organic compounds (VOCs), such as GLVs (Kessler and Baldwin, ), which recruit insect parasitoids (Turlings et al , ; Allman and Baldwin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that DLO1 catabolizes SA by converting SA to 2,3-dihydroxybenzoic acid (2,3-DHBA) and is a component of a negative feedback regulation system of SA levels during senescence [58]. Similar hydroxylation mechanisms to control levels of other plant hormones jasmonate and auxin have also been observed [59,60]. Since the induction of DLO1 in the negative feedback regulation of cytoplasmic SA levels may be critical to maintain the homeostasis of SA concentration.…”
Section: Discussionmentioning
confidence: 99%